Imports, Exports and Foreign Direct Investment Interactions and Their Effects - Santi Chaisrisawatsuk; Wisit Chaisrisawatsuk (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
This study explores how international trade and investment flows affect each other, using data from OECD and 6 ASEAN countries , and examines whether trade and investment linkages are different between developed and developing economies, or between countries that participate actively in bilateral and/or regional trade agreements.
Keywords: F1; 330; Imports; Exports; Foreign; Investment; Interactions; Effects